Delayed Hypersensitivity Reaction: An Increasingly Recognized Complication of Metal-on-Metal Total Disc Replacement. (9th August 2015) - Karnoub, Mélodie-Anne; Zairi, Fahed; Aboukais, Rabih; Assaker, Richard
Abstract : We report the case of a 32-year-old woman who presented with pain recurrence 20 months after she underwent a C5C6 metal-on-metal total replacement. Plan radiographs demonstrated a modification of the shape of the vertebral bodies making the prosthesis more protruding. Then, infection has been ruled out and patch testing revealed a strongly positive reaction for chromium and cobalt. The prosthesis has been removed and a fusion achieved using a cage filled with bone graft. She has been immediately and fully relieved from her pain. We report the radiological signs that enabled early diagnosis and treatment allowing favorable outcome.